Durability of benralizumab effectiveness in severe eosinophilic asthma patients with and without chronic rhinosinusitis with nasal polyps: a post hoc analysis from the ANANKE study - Brussino, Luisa; Aliani, Maria; Altieri, Elena; Bracciale, Pietro; Caiaffa, Maria Filomena; Cameli, Paolo; Canonica, Giorgio Walter; Caruso, Cristiano; Centanni, Stefano; De Michele, Fausto; Del Giacco, Stefano; Di Marco, Fabiano; et al. (Frontiers in Allergy, 2025)
IntroductionSevere eosinophilic asthma (SEA) often co-occurs with chronic rhinosinusitis with nasal polyps (CRSwNP), worsening asthma symptoms. Earlier studies have shown that benralizumab improves asthma outcomes with greater efficacy if patients present CRSwNP.MethodsThis post hoc analysis of the ANANKE study (NCT04272463) reports data on the long-term effectiveness of benralizumab between SEA patients with and without CRSwNP (N = 86 and N = 75, respectively) treated for up to 96 weeks.ResultsBefore benralizumab initiation, CRSwNP patients displayed longer SEA duration, greater oral corticosteroid (OCS) use and blood eosinophil count. After 96 weeks of treatment, the annual exacerbation rate (AER) decreased in both groups, with CRSwNP patients achieving considerable reductions than No-CRSwNP patients (severe AER dropped by 100% and 95.6%, respectively). While lung function improvement was comparable at week 96, CRSwNP patients showed a faster response to benralizumab, with a rise of forced expiratory volume in 1 s (FEV1) at 16 weeks that was maintained throughout the study. Median OCS daily dose decreased to 0.0 mg in both groups at 96 weeks, but benralizumab OCS-sparing effect was faster in CRSwNP patients (median OCS dose was 0.0 mg and 2.5 mg in CRSwNP and No-CRSwNP patients respectively, at 48 weeks). Although asthma control test (ACT) median scores were comparable, greater proportions of CRSwNP patients displayed well-controlled asthma (ACT ≥ 20) than No-CRSwNP patients at all time points.DiscussionThese findings show benralizumab long-term effectiveness in SEA patients with and without CRSwNP, highlighting its superior and faster-acting benefits on asthma outcomes in presence of CRSwNP.